Upaya Konservasi Hutan Mangrove di Pantai Mangrove Paluh Merbau Kec. Percut Sei Tuan, Kabupaten Deli Serdang - Harefa, Sri Aswinda; Marpaung, Viviana; Sembiring, Samariana Br; Asmara, Widya; Bancin, Girang Stevani (IAI Nasional Laa Roiba Bogor, 2025)
Mangrove forests are very important ecosystems in coastal areas of Indonesia, where people use them for various activities, such as aquaculture, fisheries, transportation, tourism, and others. However, intensive coastal activities often cause damage to mangrove ecosystems, which in turn has a direct impact on the existence of mangrove forests themselves. This human-induced damage can threaten the regeneration of fish and shrimp in offshore waters, which require mangrove forests for larval and juvenile rearing. A study conducted by the North Sumatra Environmental Agency (BLH) shows that around 90% of mangrove forests in the province are severely damaged, with the most severely affected areas including Serdang Bedagai Regency, Batubara Regency, Tanjung Balai City, Sibolga City, and Nias Regency. This research aims to reveal conservation efforts made by the community and government agencies in the mangrove forest of Paluh Merbau Mangrove Beach, Percut Sei Tuan District, Deli Serdang Regency. The required data was collected through observation and documentation, involving two representatives from the local community.